THE STATE AUTHORITIES MUST REVISE THEIR ATTITUDE TOWARDS NATIONAL MANAGEMENT STANDARDS - Kalyta, Petro (Public Management and Policy, 2025)
This article explores the deep interconnection between management system standards–including terminology–and the effectiveness of public governance in Ukraine. The author convincingly argues that the absence of harmonized management standards, particularly in terms of terminology, and the inadequate understanding of management principles are among the key causes of institutional inertia, fragmented decision-making, and low-quality public administration. Based on an analysis of current regulatory acts, international governance models (ISO, OECD, EFQM), and domestic practices, the author formulates conclusions regarding the need for a systemic renewal of management approaches. Special attention is given to the role of terminological consistency and the adequate comprehension of core management concepts as prerequisites for strategic thinking in public administration. The article also examines the influence of professional associations, expert communities, and civil society in shaping a high-quality management environment. The author proposes concrete steps to harmonize Ukrainian management standards with international norms, including the creation of a national system for terminological alignment, the modernization of educational programs, and the involvement of independent experts in the standardization process. The article highlights the necessity of designating a central executive authority responsible for overseeing and advancing management development nationwide. This interdisciplinary work integrates elements of management science, law, sociology, and public policy. It is intended for scholars, managers, government officials, and all those interested in enhancing the effectiveness of public governance through standardization tools.